Current Status of Rift Valley Fever Vaccine Development - Faburay, Bonto; LaBeaud, Angelle Desiree; McVey, D. Scott; Wilson, William C.; Richt, Juergen A. (My University, 2017)
Rift Valley Fever (RVF) is a mosquito-borne zoonotic disease that presents a substantial threat to human and public health. It is caused by Rift Valley fever phlebovirus (RVFV), which belongs to the genus Phlebovirus and the family Phenuiviridae within the order Bunyavirales. The wide distribution of competent vectors in non-endemic areas coupled with global climate change poses a significant threat of the transboundary spread of RVFV. In the last decade, an improved understanding of the molecular biology of RVFV has facilitated significant progress in the development of novel vaccines, including DIVA (differentiating infected from vaccinated animals) vaccines. Despite these advances, there is no fully licensed vaccine for veterinary or human use available in non-endemic countries, whereas in endemic countries, there is no clear policy or practice of routine/strategic livestock vaccinations as a preventive or mitigating strategy against potential RVF disease outbreaks. The purpose of this review was to provide an update on the status of RVF vaccine development and provide perspectives on the best strategies for disease control. Herein, we argue that the routine or strategic vaccination of livestock could be the best control approach for preventing the outbreak and spread of future disease.
Citation: Faburay, B.; LaBeaud, A.D.; McVey, D.S.; Wilson, W.C.; Richt, J.A. Current Status of Rift Valley Fever Vaccine Development. Vaccines 2017, 5, 29.
Keywords: Livestock Vaccination; Rift Valley Fever Virus; Vaccines